# P(x) x^4 -4x^3 +3x-1 is divided by x+2

1
by Biology1

2015-07-29T10:02:17+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
The remainder of P(x) when divided by  x + 2  is obtained by  P(x= -2)

= (-2)⁻⁴ - 4 (-2)³ + 3 (-2) -1
= 41

we can do the division as :
quotient:  x³ - 6 x² + 12 x - 21

x+2  )    x⁴  - 4 x³  + 3 x  - 1  (  x³ - 6 x² + 12 x - 21
x⁴  + 2 x³
========
- 6 x³ + 3x
- 6 x³ - 12 x²
===========
3x + 12 x²
24 x + 12 x²
==============
-21 x  -1
-21 x  - 42
============
41

===============================
A  simpler way of dividing the polynomial with x+2  is :

x + 2 )    1      -4        0        3       -1
-2      12      -24      42
==============================
1      -6       12      -21      41

So  quotient :  x³ - 6x² + 12 x - 21  and remainder  41

click on thanks button above please